2013
DOI: 10.4254/wjh.v5.i4.226
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell hepatitis with autoimmune hemolytic anemia in a nine month old infant

Abstract: Giant cell hepatitis (GCH) with autoimmune hemolytic anemia is a rare entity, limited to young children, with an unknown pathogenesis. We report the case of 9-mo old who presented with fever, diarrhea and jaundice four days before hospitalization. Physical examination found pallor, jaundice and hepatosplenomegaly. The laboratory workup showed serum total bilirubin at 101 μmol/L, conjugated bilirubin at 84 μmol/L, hemolytic anemia, thrombocytopenia and immunoglobulin G (IgG) and anti-C3d positive direct Coombs'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Secondly, the use of contraception, confirmed by 39% of women participating in the study, may reduce the absorption of vitamins, including vitamins involved in erythropoiesis. Additionally, some authors indicated that viral infections, especially of the Parvoviridae family [21] and autoimmunology diseases [22], also are the factors affecting the occurrence of anaemia. However, these factors could not be taken into account in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the use of contraception, confirmed by 39% of women participating in the study, may reduce the absorption of vitamins, including vitamins involved in erythropoiesis. Additionally, some authors indicated that viral infections, especially of the Parvoviridae family [21] and autoimmunology diseases [22], also are the factors affecting the occurrence of anaemia. However, these factors could not be taken into account in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Treating those patients is challenging and early management is crucial to prevent irreversible liver failure [ 24 ]. Relapses often occur and complete remission is difficult to obtain [ 25 , 26 ]. Additionally, those cases have an increased risk of severe to fatal infections [ 24 ].…”
Section: Warm Antibody Aiha (W-aiha)mentioning
confidence: 99%
“…10 As with the present patient, GCH-AIHA has partial response to steroids with a need for high doses of numerous immunosuppressive drugs and lack of persistent response. 4,16 Early initiation of steroids has been shown to have a beneficial effect for both liver function and AIHA. 10,13 Steroids can significantly reduce the mortality in the early active phase.…”
Section: Results Of Laboratory Tests From the Day Of Admission To Tmentioning
confidence: 99%